Use of cognitive enhancing substances by University students: a cross-sectional study - Joshi, Paliza (Curtin University, 2011)
Objectives: The purpose of this study was to determine the prevalence and patterns of use of cognitive enhancing substances (such as caffeine containing products and beverages and prescription stimulant drugs) amongst students at Curtin University. Further, to determine the potential for adverse effects from their use.Method: A cross-sectional study was conducted involving students attending the Curtin University. A sample of students was randomly selected and students were presented with an information sheet explaining the purpose and design of the study as well as their role in the study. Once they gave verbal consent to participate, they were requested to complete a questionnaire. All the completed questionnaires were entered into a dataset on a computer using the SPSS software, and analysis of the data was performed using the SPSS version 17 and SAS statistical software packages for Microsoft Windows. Statistical analysis included descriptive statistics such as frequencies and percentages or means and standard deviations. The cross-tabulation, chi-square statistic and ANOVA were used to assess the statistical significance of difference.The survey included questions regarding demographics, caffeine (consumption, reasons for use, side effects following its consumption) and prescription stimulants (use, reason for use and side effects following consumption). Further, data was collected on the perceived effectiveness of the cognitive enhancing substances by students and their level of caffeine consumption.Results: The final dataset included 526 students out of which 94.5% of surveyed students reported that they drank caffeine containing beverages. Tea and coffee were found to be the most common sources of caffeine followed by soft drinks and energy drinks. The average daily caffeine intake was estimated to be 3.0mg/Kg/day on normal days and 3.8mg/Kg/day on exam days. Females were found to consume slightly more caffeine than males. Also, there was higher caffeine intake by smokers than non-smokers.Regarding energy drinks, a greater percentage of males than females were found to consume energy drinks. The students studying health related courses were less likely than those from other faculties to consume energy drinks. Similarly, there was significant association between the smoking status and energy drinks consumption.The most frequent adverse effects experienced by students were jolt and crash followed by insomnia, and headache following caffeine intake. Moreover, more students experienced side effects following high doses of caffeine as compared to moderate and low doses. The most common self-reported reasons for consuming caffeine containing products were: to boost their energy and while studying for exams or completing major projects, and to counteract lack of sleep.Of all the respondents only 4% (n=21) reported that they used prescription stimulants (other than caffeine). Approximately 3% used stimulants together with caffeine on both normal and exam days. The prevalence of taking prescription stimulants was higher in students consuming higher doses of caffeine. The most common reported reasons for use were to improve concentration and to get high (equal percentage of 66.7% students). Most of the students stated that they experienced insomnia after the prescription stimulants intake. They also reported experiencing jolt and crash. Most of the students perceived that cognitive enhancing substances are effective in improving their energy levels.Conclusion: A substantial proportion of students in this sample were found to consume caffeine containing products. The study demonstrated that cognitive enhancing substance use was increased around times of academic stress. The students taking high doses were at higher risk to side effects. As a greater proportion of students consumed high doses of caffeine during exam period, more were at risk of adverse effects. Only a small percentage of students reported use of other stimulants, but importantly, this was more common amongst high consumers of caffeine. Further studies at other universities are required to confirm the findings of this study.